Traffic Characteristics of Abubakar Tafawa Balewa University (ATBU) Bauchi Yelwa Campus Gate and Design of Effective Mitigation Measures - N., Shonwa M.; S., Matawal D. (Lembaga Yasin AlSys, 2025)
Traffic Characteristics Research is vital for designing the required geometric features in the roadway. It includes volume of traffic, speed of traffic, and percentage of trucks or larger vehicles like bus to and fro. Traffic characteristics are broadly classified under two types viz: Road user characteristics and Vehicular characteristics. In this paper, we have studied and assess the traffic condition (volume) at Abubakar Tafawa Balewa University (A.T.B.U), Yelwa campus Gate Bauchi. The volume data was collected using manual volume count. The Traffic Volume assessment data shows that at daily basis between 7:30am to 5:30pm, the average daily traffic (cars, motorcycle, tricycle, bicycle, trucks and buses excluding pedestrians) was 5023 vehicles/day at the gate entrance and 4514 vehicles/day at the gate exit. The traffic flow map is developed and analyzed. From the results of this study it was found that there was no alarming issue from over speeding within the study area, however the higher traffic volume during the peak hour periods may require the implementation of traffic management strategies such as Tidal flow operations. After all the analysis carried out, the solutions chosen were design of a mini roundabout at the main gate to mitigate traffic congestion, eliminate traffic warden and also provide free traffic flow at the main gate intersection and design of a second gate at ATBU fence wall located 850m from Sabon kaura junction to provide easy access to parents bringing their children to international Nur/Pri and Secondary School within the campus and provide safe stopping sight distance and passing sight distance thereby providing free traffic flow.